2016
DOI: 10.1177/0961203316645205
|View full text |Cite
|
Sign up to set email alerts
|

Anti-C1q in systemic lupus erythematosus

Abstract: C1q is the first component of the classical complement pathway. Both clinically validated inhouse ELISA assays as well as commercial ELISA kits are used for detection of anti-C1q antibodies. Anti-C1q autoantibodies can be detected in a wide range of autoimmune diseases and are highly sensitive for hypocomplementemic uticarial vasculitis. In SLE, anti-C1q are strongly associated with proliferative lupus nephritis, and their absence carries a negative predictive value for development of lupus nephritis of close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 50 publications
(84 reference statements)
3
32
0
1
Order By: Relevance
“…In the single-variate analyses, anti-C1q antibodies using the standard cut-off value showed the highest OR both for active disease and for LN when using the cut-off proposed in the direction insert of the assays. This is in line with previous studies showing high clinical value in the monitoring of LN patients [ 3 7 , 11 , 24 26 ]. However, when considering the titer of the antibodies, anti-dsDNA antibodies when present at high titers showed very high OR for LN (at 390 CU, OR = 16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the single-variate analyses, anti-C1q antibodies using the standard cut-off value showed the highest OR both for active disease and for LN when using the cut-off proposed in the direction insert of the assays. This is in line with previous studies showing high clinical value in the monitoring of LN patients [ 3 7 , 11 , 24 26 ]. However, when considering the titer of the antibodies, anti-dsDNA antibodies when present at high titers showed very high OR for LN (at 390 CU, OR = 16).…”
Section: Discussionsupporting
confidence: 92%
“…This study verifies the correlation of anti-dsDNA [ 1 ] and anti-C1q autoantibodies, [ 7 , 22 ] with DA in SLE and LN. In addition, the data demonstrate the utility of a two-parametric model approach using biomarkers for assessing SLE patients for more active and severe disease, especially for patients that have, had a history of, or may develop LN.…”
Section: Discussionsupporting
confidence: 79%
“…Recently, it has been demonstrated that any de ciency in complement activation through classic and alternative pathways strongly correlated with the progression and severity of LN. Among these complement components, C1q and C3b are the most widely explored factors and have a crucial role in facilitating the clearance of immune complexes and cell residue [9,28]. In this regard, the production of antibodies against C1q may result in the formation of circulating or local complexes of C1q and anti-C1q antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased C1q production in patients with active pulmonary tuberculosis (TB) compared to latent TB has recently been reported indicating the potential use of C1q as biomarker to discriminate between patients with active TB cases from latent TB [ 16 ]. C1q has also been implicated in several immune-complex disorders such as acute glomerulonephritis [ 18 ] and acute systemic lupus erythematosus (SLE) [ 19 , 20 ] and rheumatoid arthritis [ 21 ].…”
Section: Introductionmentioning
confidence: 99%